MAIN PROBLEMS OF WORKING CAPITAL ORGANIZATION AND MANAGEMENT IN THE COMPANY - Satymbekova Katira,; Imanbayeva Zauresh Otegenkyzy,; Zhumagalieva Bakytgul,; Nurmaganbetova Begzat,; Basshieva Zhangul, (Scientific Journal of Pedagogy and Economics, 2021)
One of the main functions of the entire enterprise is the production, release of goods, its provision to the consumer, service and success. And the goal of each enterprise is to produce high-quality products, generate revenue and form its place in the market. Currently, the number of foreign and domestic enterprises working in the production sector is growing. Therefore, enterprises should always strive for innovation and consider the possibility of using advanced technologies in the production of goods. Production of goods directly related to the working capital of the enterprise. The article examines the structure of working capital within a certain enterprise and the features of its management. Considering the issues identified in the study, the main directions of working capital organization and management were proposed. Working capital can be divided into three stages of working capital maintenance. They are in the monetary, production, commodity. At the first stage of turnover, funds are advanced for raw materials, materials and labor items necessary for the production of other products. Capital is transferred from monetary form to commodity form. The second stage will produce products that will be consumed and contain the newly created value. At this stage, capital passes into the production form with the addition of labor from the commodity form, after which it passes into a new type of commodity. At the third stage, the production enterprise produces finished products and takes back the monetary form with the release of funds from the commodity form. When funds are credited to the company's current account for the products sold, the turnover is considered terminated. Since working capital is an important asset structure of the enterprise, its effective organization and management are important activities of the enterprise.